Comparative studies on the multi-component pharmacokinetics of Aristolochiae Fructus and honey-fried Aristolochiae Fructus extracts after oral administration in rats. Issue 1 (December 2017) - Yuan, Jinbin; Ren, Gang; Liang, Jian; Wang, Chong-Zhi; Yan, Zhihong; Huang, Qun; Li, Jiankang; Chen, Yang; Tang, Yi; Liu, Xiaofei; Yuan, Chun-Su
Abstract Background Aristolochiae Fructus (AF) and honey-friedAristolochiae Fructus (HAF) have been used in China for a long time as anti-tussive and expectorant drugs. Few clinical cases have been reported to be associated with the toxicity of AF and HAF, although relatively high amounts of aristolochic acids (AAs) have been found in them. Our previous experiments have verified from the chemical changes and from traditional toxicology that honey-processing can significantly reduce the toxicity of AF. To further elucidate the detoxification mechanism of honey-processing, comparative pharmacokinetics of AAs in AF and HAF are performed in this study. Methods An HPLC-MS/MS (high-performance liquid chromatography-tandem mass spectrometry) method was developed and validated for the determination of AA I, AA II, AA C, AA D and 7-OH AA I in rat plasma. The multi-component pharmacokinetics of AAs in AF and HAF extracts were investigated after the oral administration of three doses to rats. The relative pharmacokinetic parameters were compared systematically. Results The five AAs shared a similar nonlinear PK (pharmacokinetic) process. They involve rapid absorption and elimination, and they were fit into a two-compartmental open model. Some significant pharmacokinetic differences were observed between the AF and HAF groups: theC max and AUC values of AA I and AA II in the AF groups were much higher than those of the HAF groups. Conclusions Honey-frying technology can reduce the toxicity of AF by significantly decreasing the absorption of AA I and AA II. The PK parameters obtained in this work could provide valuable references for the toxicity research and clinical use ofAristolochiaceae herbs, including AF and HAF. Graphical abstract Process diagram of comparative pharmacokinetics study